A mystery in sequencing the mitochondrial DNA D-loop from blood samples of domestic Mallard duck - Wu, Zhen-Yang; Zeng, Sheng-Cheng; Luo, Yu-Zhu; Han Jianlin (Science Alert, 2011)
Domestic duck production plays a very important role in producing meat, eggs and down. To support the conservation of closely related species of wild Mallard as well as Muscovy ducks and to understand the origin, domestication process, genetic diversity as well as differentiation of domestic ducks, the partial D-loop sequence of mitochondrial DNA has been employed as the most popular molecular marker. In this study, a total of four pairs of primers located in different D-loop portions were used to amplify and sequence the partial D-loop fragment from definite domestic Mallard and Muscovy ducks together with domestic duck samples of unknown species of origin. Intensive sequencing profiles identified a homoplasmic D-loop in domestic Muscovy ducks but ‘heteroplasmic’ mtDNA D-loop fragments in domestic Mallard ducks. The results supported the presence of Numts in blood samples of domestic Mallard duck. This phenomenon has not been recognized or reported before and it can certainly confound the application of D-loop sequence as a molecular marker to genetic study of domestic Mallard duck. Further investigation on tissue specificity of the Numts and establishment of specific primers to generate the true D-loop sequences are warranted for an accurate genetic characterization and species identification of domestic ducks.